2010
DOI: 10.1051/0004-6361/200913810
|View full text |Cite
|
Sign up to set email alerts
|

J0454-0309: evidence of a strong lensing fossil group falling into a poor galaxy cluster

Abstract: Aims. We have discovered a strong lensing fossil group (J0454) projected near the well-studied cluster MS0451-0305. Using the large amount of available archival data, we compare J0454 to normal groups and clusters. A highly asymmetric image configuration of the strong lens enables us to study the substructure of the system. Methods. We used multicolour Subaru/Suprime-Cam and CFHT/Megaprime imaging, together with Keck spectroscopy to identify member galaxies. A VLT/FORS2 spectrum was taken to determine the reds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 94 publications
(160 reference statements)
1
17
0
Order By: Relevance
“…This second system, however, must be lacking in bright galaxies otherwise the magnitude gap would vanish and the system would no longer qualify as an FS, making this mode of formation unlikely, yet not impossible. Schirmer et al (2010) found J0454-0309 to consist of two systems, a sparse cluster and an infalling FS, the latter they believe will seed the FG. They also find, outside a radius of 1.5 Mpc, two filaments that extend over 4 Mpc.…”
Section: Discussionmentioning
confidence: 98%
“…This second system, however, must be lacking in bright galaxies otherwise the magnitude gap would vanish and the system would no longer qualify as an FS, making this mode of formation unlikely, yet not impossible. Schirmer et al (2010) found J0454-0309 to consist of two systems, a sparse cluster and an infalling FS, the latter they believe will seed the FG. They also find, outside a radius of 1.5 Mpc, two filaments that extend over 4 Mpc.…”
Section: Discussionmentioning
confidence: 98%
“…However, the LF slope is similar to that of clusters with σ < 800 km s −1 and BM type < II. This would suggest that these starforming dwarf galaxies are preferentially preserved in low mass environments or are destroyed in higher density systems, with many large giants, rather than a single dominant system -it is possible that most of the growth of brightest cluster galaxies may take place outside of clusters -an intriguing parallel may be offered by the 'infalling' cD galaxy in the Coma NGC4839 subgroup or the J0454-0309 fossil subgroup (Schirmer et al 2010).…”
Section: Environmental Effectsmentioning
confidence: 99%
“…Since then, several other objects have been assigned to this class in the last few years (Vikhlinin et al 1999;Jones et al 2003;Yoshioka et al 2004;Sun et al 2004;Khosroshahi et al 2004;Ulmer et al 2005;Schirmer et al 2010;Pierini et al 2011;Miller et al 2012). Jones et al (2003) estimated fossils to be Reduced spectra are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/553/A99 quite frequent, constituting 8−20% of all systems with comparable X-ray luminosity (≥10 42 erg s −1 ).…”
Section: Introductionmentioning
confidence: 99%